Cyanobacterium removal and control of algal organic matter (AOM) release by UV/H2O2 pre-oxidation enhanced Fe(II) coagulation. (15th March 2018) - Jia, Peili; Zhou, Yanping; Zhang, Xufeng; Zhang, Yi; Dai, Ruihua
Abstract: Harmful algal blooms in source water are a worldwide issue for drinking water production and safety. UV/H2 O2, a pre-oxidation process, was firstly applied to enhance Fe(II) coagulation for the removal of Microcystis aeruginosa [ M. aeruginosa, 2.0 (±0.5) × 10 6  cell/mL] in bench scale. It significantly improved both algae cells removal and algal organic matter (AOM) control, compared with UV irradiation alone (254 nm UVC, 5.4 mJ/cm 2 ). About 94.7% of algae cells were removed after 5 min UV/H2 O2 pre-treatment with H2 O2 dose 375 μmol/L, FeSO4 coagulation (dose 125 μmol/L). It was also certified that low residue Fe level and AOM control was simultaneously achieved due to low dose of Fe(II) to settle down the cells as well as the AOM. The result of L9 (3) 4 orthogonal experiment demonstrated that H2 O2 and FeSO4 dose was significantly influenced the algae removal. UV/H2 O2 induced an increase of intracellular reactive oxidant species (ROS) and a decrease in zeta potential, which might contribute to the algae removal. The total microcystins (MCs) concentration was 1.5 μg/L after UV/H2 O2 pre-oxidation, however, it could be removed simultaneously with the algae cells and AOM. This study suggested a novel application of UV/H2 O2 -Fe(II) process to promote algae removal and simultaneously control AOM release in source waters, which is a green and promising technology without secondary pollution. Graphical abstract: Highlights: UV/H2 O2 was firstly applied to enhance the algae removal by Fe(II) coagulation. Higher removal efficiency, low Fe(II) dose and control AOM simultaneously achieved. The UV/H2 O2 -Fe(II) process is green and safe without secondary pollution.